APPLICATION OF DYNAMIC STOCHASTIC GENERAL EQUILIBRIUM MODELS TO THE CASE OF THE SERBIAN ECONOMY - Urosevic, Branko; Grga, Nikola (Economic Annals, 2014)
This paper proposes a dynamic stochastic general equilibrium (DSGE) model for the Serbian economy. It is a modification of the existing models of Goodhart, Osorio and Tsomocos (2009) and Martinez and Tsomocos (2012). The model introduces important features of the Serbian economy, financial dollarization and foreign ownership of the banking system, while retaining the most important element of the reference models, financial friction. To solve the model we use Dynare, a specialized Matlab program for solving DSGE models. The model is subject to three different shocks: monetary, productivity, and regulatory, and the results are presented in the form of impulse response functions. It is concluded that the proposed platform has good characteristics, but its complete application to the case of the Serbian economy requires further research.